Frame-level bit allocation for hierarchical coding of H.265/HEVC considering dependent rate-distortion characteristics. Issue 8 (November 2016) - Liu, Minghui; Ren, Peng; Xiang, Zheng
Abstract Rate control plays an important role in video coding for rectifying the coded bit stream to meet the transmission bandwidth, which is related to two parts of bit allocation and quantization parameter acquirement. Considering that the bit allocation is a critical step due to its effect on the subsequent coding operation and rate-distortion performance, therefore in this paper an accurate H.265/HEVC frame-level bit allocation algorithm is proposed for higher coding efficiency. Concretely the feature regarding the inter-frame dependency is firstly analyzed based on the theoretical derivation. Then the hierarchically dependent characteristics are extracted and utilized to establish the bit allocation model. Experimental results show that the proposed method can guarantee a good consistency between the target bits and coded bits, where a PSNR improvement of about 0. 131 dB can be observed compared with the original H.265/HEVC bit allocation while keeping the same bit rate.